Fertility - Dufour, Anne; Illustrations by moi, Guylaine (London Hachette Illustrated, 2004)
Optimise your chances of conceiving and offer your baby the best chances of being healthy with this 60 Tips guide: face difficulties with conceiving, plan your pregnancy, exercise, nutrition and hygiene advice, relaxation techniques and much more
Include Illustrations and index
Keywords: Preconception care -- Pregnancy -- Fertility, Human